The effect of job stress on employees performance in Jabatan Belia dan Sukan Negeri Sembilan / Nur Khairun Nisah Musa - Musa, Nur Khairun Nisah (Faculty of Business and Management, 2018)
The purpose of this research was to analyse the effects of four factor including work overload, role ambiguity & role conflict working relationship and career development on job stress and employee job performance in Jabatan Belia dan Sukan Negeri Sembilan (JBSNS). To collect the primary data based on questionnaire that was directly sent to 75 respondents. The purpose of this research to investigate the effect of job stress on employees’ performance. This research is a quantitative research which had used the questionnaires as the instrument for the collection of data. The data was collected and the possible 75 respondents which was derived from the total population of 81 elements. Sample selection was based on simple random sampling method. The data collected was then evaluated by using Statistical Package for the Social Science (SPSS) Version 20 software. Using SPSS, numerous tests were converged such as reliability analysis, frequency distribution, descriptive analysis, Pearson’s correlation analysis and multiple regression. The results indicated that job stress which include work overload, role ambiguity, working relationship and career development are related to the employees’ performance.